Looking Backward to the Future - Winship, Michael (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2016)
A key moment in the emergence of the history of the book as an independent discipline occurred in summer 1980, when the participants at the international conference “Books and Society in History” in Boston gathered to issue a manifesto defining the field and calling for institutional funding to support research. Thirty-five years on, my essay draws on my experience as an editor of and contributor to the A History of the Book in America series to explore how that History came to be shaped by discussions during a series of editorial board meetings during the 1990s. I conclude by suggesting a few ways that scholars and historians might now build on those foundations for future directions in their work in book history.